CRISPR/Cas9‐mediated methoprene‐tolerant 1 knockout results in precocious metamorphosis of beet armyworm (Spodoptera exigua) only at the late larval stage. Issue 2 (12th December 2022) - Zhao, Jing; Tan, Yongan; Jiang, Yiping; Zhu‐Salzman, Keyan; Xiao, Liubin
Abstract: Juvenile hormone (JH) controls almost every aspect of an insect, especially metamorphosis. Since RNA interference works on transcripts and is often insufficient in Lepidoptera, how JH affects larval development in these insects is not well studied. Using the CRISPR/Cas9 technique, we knocked out Spodoptera exigua methoprene‐tolerant 1 ( SeMet1 ) gene of beet armyworm by modifying two sites in the coding region. However, SeMet1 knockout did not affect egg hatch rate or larval development at L1–L3 stages. In contrast to the consistent five larval instars of the control group, L4 SeMet1 mutants began to show signs of precocious metamorphosis, that is, small patches of pupal cuticle. Most L4 and all L5 SeMet1 mutants died for failing to shed their mosaic cuticles. RNA‐seq indicated that most genes encoding pupal cuticle proteins and chitinase genes were altered in SeMet1 mutant L4 larvae. SeKr‐h1, a key transcription factor in JH action was significantly down‐regulated in L3‐L5 larvae, while SeBR‐C, a pupal indicator was only upregulated in L4‐L5 larvae. These results suggested that S. exigua larvae may initially develop independently of JH, and involve SeMet1 in transducing JH signalling, leading to controlled larval metamorphosis at the late larval stage. We believe our findings will enhance better understanding of JH regulation of larval development. Abstract : This is the first study that assessed the gene functions of Spodoptera exigua methoprene‐tolerant 1 ( SeMet1 ) in a non‐model lepidopteran insect using CRISPR/Cas9 system. SeMet1 knockout did not affect egg hatch rate or larval development at L1–L3 stages. L4 SeMet1 mutants began to show signs of precocious metamorphosis, that is, pupal cuticle. S. exigua larvae may initially develop independently of JH, and involve SeMet1 in transducing JH signalling, leading to controlled larval metamorphosis at the late larval stage.